2018
DOI: 10.1038/s41416-018-0037-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cumulative incidence of adverse events in older patients with cancer undergoing first-line palliative chemotherapy: Korean Cancer Study Group (KCSG) multicentre prospective study

Abstract: WHO ICTRP number, KCT0001071.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 27 publications
3
38
3
1
Order By: Relevance
“…Table 1 provides a summary description of the included studies. There were 14 prospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44], 24 retrospective cohort studies , 2 cross-sectional studies [69,70] and 2 RCTs [71,72]. Sample sizes ranged from 24 [39] to 12,979 [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 provides a summary description of the included studies. There were 14 prospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44], 24 retrospective cohort studies , 2 cross-sectional studies [69,70] and 2 RCTs [71,72]. Sample sizes ranged from 24 [39] to 12,979 [52].…”
Section: Resultsmentioning
confidence: 99%
“…All studies were based in secondary and tertiary healthcare settings; outpatient clinics; chemotherapy or radiotherapy treatments; or inpatients. [39,51,70], three biochemical markers (haemoglobin, albumin and Creactive protein [31,32,34,37,38,40,41,45,46,49,50,58,60,61,67,[69][70][71][72]; and food and fluid measures [33,35,42]. Patient outcomes included survival, mortality, chemotherapy complications (including dosereductions and toxicities), post-operative complications (including post-operative delirium [POD], functional decline and treatment modifications) and caregiver burden.…”
Section: Resultsmentioning
confidence: 99%
“…Given that several studies have previously shown a grade 3-5 toxicity rate of 30%-50% [8][9][10][11], a conservative estimation assuming a minimum rate of grade 3-5 toxicity of 30%, with a precision of 4%, and a rate of lost patients of 10%, established a minimum sample size of 550 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although several authors have pointed out the ability of some geriatric variables to predict the development of toxicity in the older patient, such as the grip strength [39], timed up and go [18], nutritional status [10,11,40], cognition [10,18,40], IADL [10], social support [9], and others, the lack of consistency of these variables is striking among the different studies that have tried to identify predictive risk factors for chemotherapy toxicity in the older patient [41]. In fact, none of the three tools that have been proposed so far to predict toxicity in different tumors include the same geriatric variables [9][10][11]. In our series, none of the variables included in the geriatric assessment were useful to identify the risk of developing grade 3-5 toxicity as a result of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation